Subjectivity, organizational justice and performance appraisal: understanding the concept of subjectivity in leading towards employees’ perception of fairness in the performance appraisal - Low, Kah Choon; Embi, Muhamad Ali (Elsevier Ltd. Sel, 2012)
This conceptual paper addresses on the issue regarding the element of subjectivity in shaping employees’ perception of fairness in the performance appraisal. An attempt is made to understand the concept of subjectivity whereby every human judgment is subjective no matter how objective a situation can be in reality. Moreover, it is intended to trace what is the relationship between subjectivity and fairness. In an organization, fair performance appraisal is essential to ensure that no victim will be harmed or purposely being harmed. Generally, subjectivity tends to be a major unfair element causing the unfairness in the performance appraisal.